2013
DOI: 10.1055/s-0033-1343450
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Leptinemia State as a Mediator of Inflammation in Obese Adults

Abstract: Hyperleptinemia has emerged as a marker of proinflammatory status, while the adiponectin/leptin ratio has been used to identify anti-inflammatory state. In this context, the aims of the present study were to investigate the role of leptinemia, adjusted by tertiles, on inflammatory state in obese adults according to obesity degree. This is a cross-sectional study comprised of 43 obese adults. The anthropometric variables and body composition were analyzed, as well as markers of inflammation such as leptin, adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
4
6
0
1
Order By: Relevance
“…Hyperleptinemia is considered a marker of pro-inflammatory status, positively correlated with body fat, and leptin is a mediator of inflammation in obese adults [73]. In the present study, HF diet induced hyperleptinemia, while supplementation with P. tricornutum decreased the leptin level.…”
Section: Discussionsupporting
confidence: 49%
“…Hyperleptinemia is considered a marker of pro-inflammatory status, positively correlated with body fat, and leptin is a mediator of inflammation in obese adults [73]. In the present study, HF diet induced hyperleptinemia, while supplementation with P. tricornutum decreased the leptin level.…”
Section: Discussionsupporting
confidence: 49%
“…23 In the human study, hyperleptinemia has been reported to be one of the major factors of proinflammatory status. 12 Therefore, leptin may contribute as one of the many hits on the development of NASH.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is an adipocytokine and considered to be a mediator of inflammation. 12 Some findings were reported to associate with inflammation and oxidative stress in liver disease. Therefore, leptin has been suggested to have an important role in the development of liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to animals fed ND, mice fed on HFD revealed hyperleptinemia. Although leptin is known to be a potent insulin sensitizer and can improve glucose tolerance, leptin resistance might occur in response to HFD, and both hyperleptinemia and inflammation have been proposed as causative mechanisms [ 24 , 30 ].…”
Section: Discussionmentioning
confidence: 99%